Compatibility of bioplaguicides clibadium sylvestre and trichoderma harzianum as an alternative in ecological control of plage - Azabache, José (2024)
Clibadium sylvestre is a plant that in some areas of the Amazon is used in artisanal fishing. Trichoderma harzianum is a biocontroller of fungi and phytopathogenic nematodes. The objective of this research was to evaluate the effect of the ethanolic extract of C. sylvestre seeds on the growth of T. harzianum to determine the compatibility between both biopesticides. The seeds were obtained from C. sylvestre from the department of San Martín, Peru, dried at 40°C for 48 h of exposure, pulverized, and subjected to extraction with 70% ethanol, and finally the product obtained was decanted and filtered. The bioassays with T. harzianum were carried out on Sabouraud Dextrose Agar (SDA) with the ethanolic extract of C. sylvestre at 125 to 1000 mg•L-1. T. harzianum mycelium was seeded in the central part of each Petri dish with SDA, incubated at room temperature, measuring the diameter of the colony every 12 h. The parameters evaluated in T. harzianum were colony diameter (mm) up to 84 h and growth speed (mm•h-1) up to 100 mm in diameter. The colony diameter and growth speed were different from the control, indicating that the ethanolic extract of C. sylvestre acts as an inhibitor of T. harzianum. It is concluded that both biopesticides are not compatible to be used together in ecological pest management.